Rendahnya Tingkat Keberhasilan Mediasi di Pengadilan Agama Bantul Tahun 2018-2020: Studi Terhadap Analisis Efektivitas Peran Mediator di Pengadilan Agama Bantul - Rahyu, Putri; Sugitanata, Arif (Al-Hukama': The Indonesian Journal of Islamic Family Law, 2022)
This article discusses the low success rate of mediation at the Bantul Religious Court in 2018-2020: a study of the analysis of the role of mediators at the Bantul Religious Court. The focus of this study is to analyze the reasons or factors for the low success of mediation by mediators at the Bantul Religious Court by utilizing the concept of legal sociology whose scalpel uses the theory of legal effectiveness, legal culture and conflict resolution. The results of this study indicate that the effectiveness of the successful role of the mediator is influenced by seven factors namely First, the parties are determined to divorce, Second, the degree of difficulty of the case. Third, the level of public awareness. Fourth, the mediation time is too short. Fifth, Mediation is only a formality. Sixth, the good faith of the parties. Seventh, the ability of the mediator. [Artikel ini membahas mengenai rendahnya tingkat keberhasilan mediasi di Pengadilan Agama Bantul tahun 2018-2020: studi terhadap analisis peran mediator di Pengadilan Agama Bantul. Fakus dari kajian ini ialah menganalisa alasan atau faktor rendahnya keberhasilan mediasi oleh mediator di Pengadilan Agama Bantul dengan memanfaatkan konsep sosiologi hukum yang pisau bedahnya menggunakan teori efektivitas hukum, budaya hukum dan resolusi konflik. Hasil penelitian ini menunjukkan bahwa efektifitas keberhasilan peran mediator dipengaruhi oleh tujuh faktor yakni Pertama, Para pihak sudah bersikukuh untuk bercerai, Kedua, Tingkat kesulitan kasus. Ketiga, Tingkat kesadaran masyarakat. Keempat, Waktu mediasi terlalu singkat. Kelima, Mediasi hanya sebagai formalitas. Keenam, Itikad baik para pihak. Ketujuah, Kemampuan mediator.]